A method for preparing high-performance PVDF-based film based on nanosecond electric pulse induction

The preparation of PVDF-based films in quartz glass grooves by nanosecond electrical pulse induction method solves the problem of difficulty in preparing high-β-phase content films in the prior art, and achieves high-performance and low-cost film preparation.

CN115910606BActive Publication Date: 2025-02-07CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211627834.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-17
Publication Date
2025-02-07
Estimated Expiration
2042-12-17

AI Technical Summary

Technical Problem

It is difficult to effectively prepare PVDF-based films with high beta phase content in the prior art, and the preparation process is complex, costly and low efficiency.

Method used

PVDF-based films were prepared by nanosecond electrical pulse induction method. By applying nanosecond electrical pulses and high temperature treatment in quartz glass grooves, dipole steering in P(VDF-HFP) polymer was induced to form high β-phase content. film.

Benefits of technology

A PVDF-based film with a β-phase content of more than 80%, a grain size of less than 10 nm, a charge and discharge energy storage density of about 14 J/cm3, and a charge and discharge energy storage efficiency of more than 60%, simplifying the process and reducing costs and energy Consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115910606B_ABST
    Figure CN115910606B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-performance PVDF-based energy storage film based on nanosecond electric pulse induction, the steps of which include: preparing a polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP) solution, taking an appropriate amount of the solution and evenly dropping it into a cleaned glass groove, and applying different nanosecond electric pulses at a certain temperature. After naturally cooling to room temperature, the film is quenched and then placed in a vacuum drying oven for drying to further remove moisture and residual solvent. The present invention controls the amplitude, pulse width, frequency, pressurization time, vacuum drying time and temperature of the nanosecond electric pulse and customizes the size of the groove, and adopts a solution casting method to obtain β P(VDF‑HFP) films with high phase content and excellent energy storage performance, β The phase content is more than 80%, and the charge and discharge energy density is 14 J / cm 3 , the charge and discharge efficiency can reach more than 60%. The present invention eliminates the complicated secondary process, is simple to operate, greatly saves production costs, and has obvious advantages and application prospects in the preparation of high-performance PVDF-based energy storage films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-performance energy storage film capacitors, and in particular to a method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction. Background Art

[0002] PVDF has attracted wide attention in the field of film capacitors due to its advantages such as high dielectric constant, strong anti-aging and high tensile strength. It is considered to be the most promising dielectric material for high energy density capacitors. Its copolymer P (VDF-HFP) introduces low dipole moment monomers into -VDF to reduce the ferroelectric domain size of PVDF, thereby improving its polarization and energy storage performance. P (VDF-HFP) has a variety of crystal structures like PVDF. The three most common crystal phases are α , β and γ ,in β The phase belongs to the orthorhombic crystal system and is an all-trans TTTT configuration, which has stronger polarity and ferroelectricity. β Phase PVDF has a larger dielectric constant than other phases of PVDF-based polymers and is more suitable for preparing capacitor films. α The most stable and common phase in P(VDF-HFP) belongs to the orthorhombic system and is TG + TG - Conformation. α The dipole moments in the phase molecular chains are reversed, resulting in a net dipole moment of zero, showing a non-polar characteristic. Most conventional preparation methods can only obtain α phase-based P(VDF-HFP) film, so how to prepare high β The phase content of PVDF-based polymer films has always been a major challenge in this field.

[0003] In order to obtain high-performance P(VDF-HFP) films, researchers at home and abroad have developed a series of preparation methods to improve the β Phase content, including stretching, electrospinning, high-pressure annealing crystallization, etc. The prepared PVDF-based film is usually subjected to secondary processing, and the internal polymer of P (VDF-HFP) is turned by external force. These operation methods are not only very complicated, but also require high external force, and have high requirements for preparation process and equipment, high preparation cost, low efficiency, and the prepared PVDF-based film β The phase content is unstable. At present, high-performance and high-efficiency nanoparticles are prepared by using external nanosecond pulse electric fields to induce β There is little research on PVDF-based films with different phase contents. Summary of the invention

[0004] In view of the above problems existing in the prior art, the problem to be solved by the present invention is: how to prepare β PVDF-based films with high phase content and stable performance.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction, comprising the following steps:

[0006] S1: Prepare polyvinylidene fluoride-hexafluoropropylene P (VDF-HFP) solution using N,N-dimethylformamide DMF;

[0007] A quartz glass groove is used, and copper foil is attached to both sides of the groove wall as a conductive electrode. After cleaning, it is put into an oven for standby use. The polyvinylidene fluoride-hexafluoropropylene P (VDF-HFP) powder in S1 is magnetically stirred at room temperature until it is completely dissolved in the DMF solvent to obtain P (VDF-HFP) solutions of different concentrations, and then the solution is evenly dripped into the quartz glass groove with a syringe;

[0008] S2: Apply nanosecond electric pulses at both ends of the electrodes, remove the voltage and continue heating in an oven until the solvent evaporates completely to obtain a P(VDF-HFP) film. Usually, heating is continued for 12 hours.

[0009] S3: After quenching, the P(VDF-HFP) film obtained in S2 is placed in a vacuum drying oven for vacuum drying.

[0010] The present invention adopts nanosecond electric pulse assisted solution casting method to prepare PVDF-based energy storage film in a customized quartz glass groove, and the thickness of the final P (VDF-HFP) film is controlled within 10 ± 3 μm. β The phase is more than 80%, the grain size is less than 10 nm, and the charge and discharge energy storage density is about 14 J / cm 3 , a P (VDF-HFP) film with a charge and discharge energy storage efficiency greater than 60%. The present invention eliminates the complicated secondary process, has a simple and convenient process, greatly saves production costs, has low energy consumption, is safe and low-pollution, and can be widely used in the preparation of PVDF-based energy storage films.

[0011] Preferably, the concentration of the P(VDF-HFP) solution in S1 is 20-70 mg / mL, so as to control the final film thickness to be around 10 μm.

[0012] Preferably, the quartz glass groove in S1 is 10-50 mm long, 10-50 mm wide, and 1-5 mm deep, to ensure uniform final film formation.

[0013] Preferably, the nanosecond electric pulse amplitude in S2 is 100-12000 V, the pulse width is 10-800 ns, and the frequency is 1-10000 Hz. A suitable electric field is used to induce dipole steering of polar molecules in the P(VDF-HFP) polymer while preventing turbulence from forming in the liquid matrix.

[0014] Preferably, the nanosecond electric pulse application time in S2 is 5-180 minutes to ensure that the matrix achieves phase change and maintains stability.

[0015] Preferably, the quenching process in S3 is to heat the P(VDF-HFP) film obtained in S2 in a 200-250°C oven for 5-10 min and then immediately put it in ice water. Subsequently, the quenched P(VDF-HFP) film is placed in a 50-120°C vacuum drying oven for vacuum drying for 10-60 h to further remove residual moisture and solvent, and to gradually cool the P(VDF-HFP) from high temperature to obtain a stable crystalline structure.

[0016] Compared with the prior art, the application of nanosecond electric pulses has the following great impact on the method of the present invention, and has at least the following advantages:

[0017] 1) Nanosecond electric pulses can turn P(VDF-HFP) polymer under low electric field, obtaining more than 80% β The phase content is small, the operation is simple, and it is beneficial to industrial production.

[0018] 2) The grain size of the P(VDF-HFP) film prepared by the method of the present invention is less than 10 nm, which is beneficial to improving its electrical breakdown field strength.

[0019] 3) The dielectric properties of the P(VDF-HFP) film prepared by the method of the present invention are improved, the dielectric constant reaches 11, and the dielectric loss is less than 0.02.

[0020] 4) The energy storage performance of the P(VDF-HFP) film prepared by the method of the present invention is improved, and the charge and discharge energy storage density is about 14 J / cm 3 , the charging and discharging energy storage efficiency is greater than 60%.

[0021] 5) P(VDF-HFP) has a polar unit -CH2-CF2-. Under the action of an external electric field, the polar group rotates in the direction of the nanosecond pulse electric field. In the liquid matrix, the P(VDF-HFP) chain is randomly coiled with a chaotic configuration and a loose lattice. At this time, the dipole orientation can be induced under the nanosecond pulse electric field. This patent uses a unipolar pulse electric field to make the dipoles rotate in the same direction, and finally obtains a high β Phase content.

[0022] 6) Under the dual effects of nanosecond electric pulses and high temperature, the P(VDF-HFP) molecular chain moves faster and the polarizability of the dipole increases. After the external electric field is removed, there is no other external field effect. At this time, the P(VDF-HFP) chain maintains the planar zigzag configuration after the dipole orientation. As the solvent gradually evaporates, P(VDF-HFP) forms a tightly packed stable lattice that is not easy to change, and after the second step of vacuum drying and annealing, the molecular chain forms a regular planar zigzag configuration. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a structural diagram of a quartz glass groove, where 1 is a heating plate, 2 is quartz glass, and 3 is copper foil.

[0024] Figure 2 This is the XRD peak fitting diagram of sample 1.

[0025] Figure 3 This is the XRD peak fitting diagram of sample 6.

[0026] Figure 4 This is a comparison chart of the energy storage characteristics of sample 1 and sample 6. DETAILED DESCRIPTION

[0027] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0028] Embodiment 1, a method for preparing a high-performance PVDF-based film, comprising the following steps:

[0029] (1) Polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP) (hexafluoropropylene mass fraction is 10%) and N,N-dimethylformamide (DMF) were used to obtain a 24 mg / mL P(VDF-HFP) / DMF solution. A customized quartz glass groove was used with a length of 30 mm, a width of 20 mm, and a depth of 1 mm. Magnetic stirring was performed at room temperature for 12 h until P(VDF-HFP) was completely dissolved. The quartz glass groove was cleaned and placed in an oven for later use.

[0030] (2) Use a syringe to take 1 mL and evenly drop it into the quartz glass groove to obtain a pure P(VDF-HFP) film. Continue heating in an oven for 12 h to complete the first step of drying. Place the obtained film in a 200 °C oven and heat for 10 min for quenching, then place it in a 105 °C vacuum drying oven and continue drying for 24 h to obtain a P(VDF-HFP) film, i.e., Sample 1.

[0031] Embodiment 2, a method for preparing a high-performance PVDF-based film, comprising the following steps:

[0032] (1) Polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP) (hexafluoropropylene mass fraction is 10%) and N,N-dimethylformamide (DMF) were used to obtain a 20 mg / mL P(VDF-HFP) / DMF solution. The solution was stirred magnetically at room temperature for 12 h until the P(VDF-HFP) was completely dissolved. A customized quartz glass groove was used with a length of 30 mm, a width of 15 mm, and a depth of 2 mm. Copper foil was cut into appropriate sizes and attached to both sides of the groove wall as conductive electrodes. After cleaning, it was placed in an oven for later use.

[0033] (2) Use a syringe to take 1 mL of the solution and evenly drop it into the quartz glass groove. Apply an electric pulse with an amplitude of 50 V, a pulse width of 10 ns, and a frequency of 10 Hz to both ends of the electrode. After continuous pressurization for 5 minutes, stop the pressurization and continue heating in an oven for 12 hours to obtain a P(VDF-HFP) film.

[0034] (3) The P(VDF-HFP) obtained in (2) was placed in a 200 °C oven for heating for 10 min and then immediately placed in ice water for quenching. It was then placed in a 50 °C vacuum drying oven for further drying for 12 h to obtain a P(VDF-HFP) film, i.e., Sample 2.

[0035] The preparation steps of Example 3-20 are the same as those of Example 2, and the only difference is the selection of formulation and process parameters, as shown in Table 1:

[0036] For the convenience of description, the nanosecond electric pulse application time in S2 is recorded as t1, the P (VDF-HFP) film quenching time in S3 is recorded as t2, and the time for the P (VDF-HFP) film to be placed in a vacuum drying oven for vacuum drying is recorded as t3.

[0037] Table 1 Process parameters of Examples 1-20

[0038]

[0039] For the electric pulse assisted solution casting method, similar experimental results can be achieved by slightly adjusting the parameter indicators.

[0040] The performance tests of the P(VDF-HFP) film samples obtained in Examples 1 to 20 were performed:

[0041] 1. P(VDF-HFP) film β Phase content test

[0042] 2. P(VDF-HFP) film energy storage performance test

[0043] In order to demonstrate the beneficial effects of the present invention, the inventors tested and analyzed the P(VDF-HFP) film prepared by the present invention. The main experimental data results are shown in Table 2.

[0044] Table 2 Different P(VDF-HFP) film samples β Phase content and energy storage properties

[0045] Sample Phase content / % <![CDATA[Charge-discharge energy storage density / J / cm 3 > Charge and discharge efficiency / % Sample 1 35 6 50 Sample 2 43 8 55 Sample 3 62 14 60 Sample 4 70 12 65 Sample 5 82 10 58 Sample 6 80 13 59 Sample 7 75 13 57 Sample 8 59 11.7 60 Sample 9 70 11 60 Sample 10 50 7.8 52 Sample 11 30 5 70 Sample 12 83 14.4 62 Sample 13 38 7.2 68 Sample 14 37 7 72 Sample 15 80 13.6 58 Sample 16 57 6.8 75 Sample 17 65 8.4 52 Sample 18 68 10.5 57 Sample 19 55 9.3 50 Sample 20 45 8.7 55

[0046] From Tables 1 and 2, it can be seen that the electric pulse parameters (electric field amplitude, nanosecond width, frequency, pressing time and groove size, etc.) and the vacuum drying time and temperature in the electric pulse assisted solution casting process have an important influence on the properties of the P(VDF-HFP) film. β The phase content and energy storage properties have an important influence. The basic rule is: β The phase content first increases and then decreases with the increase of the electric field amplitude. The energy storage characteristics change accordingly. Electric pulse amplitudes that are too high or too low will lead to a decrease in energy storage performance, so it needs to be controlled within an appropriate range. In S1, the appropriate solution concentration needs to be controlled according to the groove size of the quartz glass, and the film thickness is controlled to be around 10 μm. The prepared film is too thick or too thin, which affects the energy storage performance of the film. In S2, the smaller the size of the quartz glass groove, the more difficult it is to apply the pulse voltage, resulting in the P(VDF-HFP) film. β Phase content and energy storage performance decreased, while too large size will also affect the thickness of P(VDF-HFP) film. Vacuum drying in S3 is a key step in annealing crystallization. Too short or too long time will lead to poor comprehensive performance of the film.

[0047] Figure 1 Schematic diagram of quartz glass groove. Figure 2 and Figure 3 The XRD peak fitting diagrams of the samples of Example 1 and Example 6 are respectively obtained. From the diagrams, it can be seen that the P (VDF-HFP) film prepared with the assistance of a suitable nanosecond electric pulse in the present invention has a good β The phase content can reach over 80%, which is a significant improvement compared to the P(VDF-HFP) film without nanosecond electric pulses applied. Figure 4 It can be seen that the charge and discharge density of the P(VDF-HFP) film made with the assistance of nanosecond electric pulses reaches 14 J / cm 3 The charge and discharge efficiency reaches 60%, which is higher than that of the P(VDF-HFP) film prepared without applying nanosecond pulses.

[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing high-performance PVDF-based films based on nanosecond electric pulse induction, characterized in that: The steps include: S1: Prepare polyvinylidene fluoride-hexafluoropropylene P (VDF-HFP) solution using N,N-dimethylformamide DMF; A quartz glass groove is used, and copper foil is attached to both sides of the groove wall as two conductive electrodes, and then placed in an oven for standby use. The polyvinylidene fluoride-hexafluoropropylene P (VDF-HFP) powder in S1 is magnetically stirred at room temperature until it is completely dissolved to obtain P (VDF-HFP) solutions of different concentrations, and the solutions are evenly dripped into the quartz glass groove with a syringe; S2: Apply nanosecond electric pulses at both ends of the electrodes, remove the voltage and continue heating until the solvent evaporates completely to obtain a P(VDF-HFP) film; S3: After quenching, the P(VDF-HFP) film obtained in S2 is placed in a vacuum drying oven for vacuum drying.

2. A method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction according to claim 1, characterized in that: The concentration of the S1 P(VDF-HFP) solution is 20-70 mg / mL.

3. The method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction according to claim 1, characterized in that: The quartz glass groove in S1 is 10-50 mm long, 10-50 mm wide, and 1-5 mm deep.

4. The method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction according to claim 1, characterized in that: The nanosecond electric pulse amplitude in S2 is 100-12000 V, the pulse width is 10-800 ns, and the frequency is 1-10000 Hz.

5. The method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction according to claim 1, characterized in that: The nanosecond electric pulse application time in S2 is 5-180 minutes.

6. The method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction according to claim 1, characterized in that: The quenching process in S3 is to place the P(VDF-HFP) film obtained in S2 in an oven at 200-250° C. and heat it for 5-10 min, and then immediately place it in ice water.

7. The method for preparing a high-performance PVDF-based film based on nanosecond electric pulse induction according to claim 1, characterized in that: The vacuum drying in S3 is performed in a vacuum drying oven at 50-120° C. for 10-60 h.